Peranan PT IMC Ship Management Selaku Auditor Internal Terhadap Safety Management System di MV. Dewi Shinta Manggala - Rizal Ardiansyah; Dian Junita Arisusanty; Teguh Pribadi (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Internal audit activities are carried out to meet and implement the Safety Management System (SMS) rules so that safety on board ships is implemented in accordance with the ISM Code. In addition, an internal audit conducted by a shipping company can minimize the findings of an external audit of the Safety Management System (SMS). The purpose of this research is to find out the implementation process, obstacles and solutions for the implementation of MV internal audit. Dewi Shinta Manggala. The method carried out in this study is qualitative descriptive. Data collection was carried out by in-depth interviews, observations, and documentation. The results of the study show that the obstacles faced in the obstacles experienced in the internal audit process are the unsuitable time between the ship's schedule and the auditor resulting in delays, crew ratings that are not optimal in implementing the Safety Management System (SMS), and the crew's understanding of the Safety Management System (SMS) on board the ship which is considered to be still lacking. So that the efforts that must be made, namely the company's internal parties communicate well with each other, the company gives strict sanctions to crews who do not optimally implement SMS, the company requires crews to attend SMS training.